2003
DOI: 10.1038/nature02129
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and conserved RNA binding of the PAZ domain

Abstract: The discovery of RNA-mediated gene-silencing pathways, including RNA interference, highlights a fundamental role of short RNAs in eukaryotic gene regulation and antiviral defence. Members of the Dicer and Argonaute protein families are essential components of these RNA-silencing pathways. Notably, these two families possess an evolutionarily conserved PAZ (Piwi/Argonaute/Zwille) domain whose biochemical function is unknown. Here we report the nuclear magnetic resonance solution structure of the PAZ domain from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
284
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(294 citation statements)
references
References 29 publications
8
284
0
2
Order By: Relevance
“…8 Argonaute2 (Ago2), one of the main components of RISC, is responsible for mRNA cleavage in the miRNA pathway. [17][18][19] In this regard, we estimated the amount of miR-143 included in the RISC after the transfection of DLD-1 cells with Tumor-suppressive effect of chemically modified synthetic miR-143 in vivo To examine the growth-suppressive effect of miR-143 in vivo, we administered miR-143BP/3 0 -2 M by intratumor injection (0.15 mg per mouse) into nude mice bearing DLD-1 tumors ( Figure 3A). After the inoculation of the DLD-1 cells into the mice (day 0), we injected the modified synthetic miR-143 at day 10, when the tumor volume had reached 300 mm 3 and then evaluated the tumor size at day 38.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Argonaute2 (Ago2), one of the main components of RISC, is responsible for mRNA cleavage in the miRNA pathway. [17][18][19] In this regard, we estimated the amount of miR-143 included in the RISC after the transfection of DLD-1 cells with Tumor-suppressive effect of chemically modified synthetic miR-143 in vivo To examine the growth-suppressive effect of miR-143 in vivo, we administered miR-143BP/3 0 -2 M by intratumor injection (0.15 mg per mouse) into nude mice bearing DLD-1 tumors ( Figure 3A). After the inoculation of the DLD-1 cells into the mice (day 0), we injected the modified synthetic miR-143 at day 10, when the tumor volume had reached 300 mm 3 and then evaluated the tumor size at day 38.…”
Section: Resultsmentioning
confidence: 99%
“…25 Moreover, it has been shown that the 3 0 -overhang region of a guide strand of miRNA is recognized by the PAZ (Piwi/Argonaute/ Zwille) domain in the Ago2, and the 2-nucleotide MicroRNA-143 and -145 in human colorectal tumors Y Akao et al 3 0 -overhang is accommodated into a binding pocket composed of hydrophobic amino acids in the PAZ domain. [17][18][19] Therefore, we consider that BP at the 3 0 -overhang region may be associated with the PAZ domain of Ago2. 13,14 These findings were reflected by the evidence that the protein level of ERK5, one of the major targets of miR-143, was downregulated in accordance with the activities of the various synthetic miR-143s with modified passenger sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structures of bacterial and archaeal Argonaute proteins and the PAZ domains of eucaryotic Argonautes revealed that the PAZ domain binds the short single-stranded 3 0 'tails' characteristic of an siRNA. It has been postulated that the PAZ domain initiates incorporation of a small RNA into RISC by binding the single-stranded 2nt 3 0 overhang of an siRNA or miRNA duplexes (Lingel et al, 2003;Song et al, 2003Song et al, , 2004Yan et al, 2003;Ma et al, 2005). More remarkably, these structural studies revealed that the key to understanding the sequence-specific activity of RISC resides in the structure of the PIWI domain, whose three-dimensional fold clearly places in the RNase H enzyme family of nucleic-acid-directed RNA-endonucleases Ma et al, 2005;Parker et al, 2005;Yuan et al, 2005).…”
Section: Risc Formationmentioning
confidence: 99%
“…This region would be occupied with target strand mismatches. Finally, the 3′ end of the RNA is bound by the PAZ domain, with most of the relevant interactions occurring between the final phosphate and sugar in a sequence nonspecific manner [27,80,81].…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
“…This region would be occupied with target strand mismatches. Finally, the 3′ end of the RNA is bound by the PAZ domain, with most of the relevant interactions occurring between the final phosphate and sugar in a sequence nonspecific manner [27,80,81].With regard to catalysis, the PIWI domain contains the enzyme's DEDH active site, which requires Mg 2+ for activity [78,82,83] (Fig. 2a).…”
mentioning
confidence: 99%